Confucian Social Ethics amid Modernization: An Exploratory Study of Generation Z Adherents in Medan, Indonesia - Nasution, Anya Dwi Aprilia; Syahminan, Mhd. (Jurnal Sosiologi Agama Indonesia (JSAI), 2026)
Modernization and digitally mediated communication have changed the settings in which inherited religious ethics are interpreted and practiced. Existing studies of Confucianism in Indonesia have largely emphasized doctrinal and historical questions, leaving the everyday ethical interpretations of young adherents less examined. This study explores how three Generation Z Confucian adherents in the Jalan Gunung Krakatau community of Medan understand and apply Confucian values in family, community, and digital interactions, as well as how they perceive the challenges of modernization. The study used an exploratory qualitative descriptive design. Participants were selected purposively, and data were collected through face-to-face semi-structured interviews conducted on May 8, 2026, with contextual field notes used to document the interview setting. The data were coded and organized thematically. The participants understood Ren, Yi, Li, Zhi, Xin, and Xiao as an interconnected moral framework rather than as abstract doctrine. Filial respect, compassion, practical assistance, tolerance, appropriate communication, considered judgment, and trustworthiness emerged as the main expressions of social ethics in their accounts. Modernization was not described as eliminating these values; it created tensions between personal aspirations and relational duties, traditional propriety and informal communication, and technological opportunity and ethical responsibility. Within this bounded setting, the continuity of Confucian ethics rested on reinterpretation and everyday application rather than unchanged repetition. These findings provide a context-specific account and are not intended to represent Confucian Generation Z more broadly.